Pengembangan Instrumen Five-Tier NewtonÃ¢â¬â¢s Laws Test (5TNLT) Untuk Mengidentifikasi Miskonsepsi dan Penyebab Miskonsepsi Siswa - Imas Rosita; Winny Liliawati; Achmad Samsudin (Department of Physics Education, Universitas Mataram, 2020)
This study aims to identify students' misconceptions on Newton's Law using the Five-Tier Newton's Laws Test (5TNLT) instrument. The process of identifying misconceptions is carried out as one of the first steps to overcome student misconceptions. The method used in this study uses the 4D model (Defining, Designing, Developing, and Disseminating). Participants involved in this study consisted of 327 students (198 female and 129 male), who came from 2 public high schools and 1 private high school in Bandung. Based on the research, it was found that the 5TNLT instrument developed by the researcher could be used to identify misconceptions and causes of students' misconceptions on Newton's Law. All items on the 5TNLT instrument are valid and reliable enough to measure student misconceptions. The highest percentage of misconception categories is shown in the MC-PT (Misconception from personal thoughts) category, which is 50.21%, while the smallest percentage is shown in the MC-I (Misconception from the internet) category, which is 14.82%.